Parental Birth-Related PTSD Symptoms and Bonding in the Early Postpartum Period: A Prospective Population-Based Cohort Study - Stuijfzand, Suzannah; Garthus-Niegel, Susan; Horsch, Antje (Frontiers in Psychiatry, 2020)
The parent-infant bond following childbirth is an important facilitator of optimal infant development. So far, research has mainly focused on mother-infant bonding. Data on fathers are still sparse. Parental mental health, such as posttraumatic stress symptoms (PTSD), may influence mother-infant relations and/or interactions. There is evidence that both parents can experience PTSD symptoms following childbirth (PTSD-CB). The aim of this study is to investigate the prospective relationship between parental PTSD-CB symptoms at 1 month postpartum and perceived parent-infant bonding at 3 months postpartum, while adjusting for antenatal confounders. A subsample was used for this study (nTotalsample 488, nmothers = 356, nfathers = 132) of an ongoing prospective cohort study. Future parents awaiting their third trimester antenatal appointments at a Swiss university hospital were recruited. Self-report questionnaires assessed PTSD-CB symptoms and psychological distress at 1 month postpartum, and parent-infant bonding at 3 months postpartum. Confounders included antenatal PTSD symptoms and social support measured via self-report questionnaires, and gestity and gestational age, extracted from medical records. Using structural equation modeling, the predictive ability of PTSD-CB symptoms at 1 month postpartum on parent-infant bonding at 3 months postpartum was assessed for both parents respectively. Maternal PTSD-CB symptoms at 1 month postpartum were found to be negatively prospectively associated with mother-infant bonding at 3 months postpartum; however, this effect disappeared after adjusting for psychological distress at 1 month postpartum. No such effects were found for fathers. There was no evidence of mediation of the relationship between parental PTSD-CB symptoms at 1 month postpartum and parental-infant bonding at 3 months postpartum via psychological distress at 1 month postpartum. However, such a mediation was found for maternal intrusion and hyperarousal symptom subscales. Results expand the current literature on the impact of PTSD-CB on parent-child relations to also include fathers, and to a community sample. Any adverse effects of mental health symptoms on parent-infant bonding were evidenced by 3 months postpartum only for mothers, not fathers. Our results may inform the development of prevention/intervention strategies.